Indazole-5-amine (AIA) as competing corrosion coating to Benzotriazole (BTAH) at the interface of Cu: A DFT and BOMD case study - Samal, Pragnya Paramita; Singh, Chandrodai Pratap; Tiwari, Shivani; Shah, Vaishali; Krishnamurty, Sailaja (Computational and Theoretical Chemistry, 2024)
This study compares three organic compounds-benzotriazole (BTAH), imidazole (IM), and indazole-5-amine (AIA)-as corrosion inhibitors for copper substrates. Using Density Functional Theory (DFT) and Born-Oppenheimer Molecular Dynamics (BOMD) calculations, it identifies AIA as a promising and cost-effective alternative to the toxic BTAH. The adsorption strength on Cu(1 0 0) surfaces is ranked AIA>BTAH>IM for both neutral and deprotonated forms. These findings are supported by electronic parameter studies, including Bader charge analysis, density of states (DOS), charge density differences (CDD), and frontier molecular orbital analysis. AIA shows the best adsorption in a parallel orientation at the top site. Packing studies reveal that hydrogen bonding stabilizes the interaction energies within self-assembled AIA aggregates. Organometallic complexation studies reveal that deprotonated BTAH exhibits higher interaction energy with a single Cu atom compared to AIA when bonded through the carbon end, consistent with the findings from BOMD studies. However, on periodic Cu surfaces, AIA outperforms BTAH molecules as seen from adsorption energies. This investigation highlights AIA's potential as a superior and more economical corrosion inhibitor for copper.
Keywords: Adsorption; Born-Oppenheimer molecular dynamics; Corrosion inhibition; Density functional theory; Indazole derivatives